The Use of Fish Waste Based Organic Fertilizer to Improve the Growth of Balinese Red Rice (Oryza Sativa L Cv. Barak Cenana) - I Dewa Gede Cahyadi Kusuma; Ni Luh Suriani; Yan Ramona (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2021)
In recent years, wastes have been reprocessed into useful products, such as organic fertilizer. The application of organic fertilizers in farming practices can produce agricultural products that are safe for human health and the environment. The objective of this study was to investigate the effect of liquid organic fertilizer made from fish waste on the growth of Bali red rice seedlings. A Complete Randomized Design (CRD) consisted of 8 treatments with 5 replications was applied in this experiment. These included immersing of rice seeds in fish waste fertilizer with concentrations of 0.5% = P1, 1% = P2, 1.5% = P3, 2% = P4, 2.5% = P5 and 3% = P6 with volume/volume ratio (v/v), prior to soaking. Rice seeds without immersion in this fertilizer (C0) and those immersed in PGPR bacterial suspension only (C1) served as nil control and control treatments, respectively. The results showed that the application of 2.5% fish waste fertilizer produced the highest results, following measurement of parameters, including the percentage of germination (88.18%), plant height (28.78 cm), and root length (20, 74 cm) on day 15 after sowing.